Nanoindentation Response Analysis of Thin Film Substrates-II: Strain Hardening-Softening Oscillations in Subsurface Layer - Kanders Uldis (Latvian Journal of Physics and Technical Sciences, 2017)
We have extracted stress-strain field (SSF) gradient and divergence representations from nanoindentation data sets of bulk solids often used as thin film substrates: bearing and tooling steels, silicon, glasses, and fused silica. Oscillations of the stress-strain field gradient and divergence induced in the subsurface layer by the nanoindentation have been revealed. The oscillations are especially prominent in single indentation tests at shallow penetration depths, h<100 nm, whereas they are concealed in the averaged datasets of 10 and more single tests. The amplitude of the SSF divergence oscillations decays as a sublinear power-law when the indenter approaches deeper atomic layers, with an exponent −0.9 for the steel and −0.8 for the fused silica. The oscillations are interpreted as alternating strain hardening-softening plastic deformation cycles induced in the subsurface layer under the indenter load.